FAKTOR FUNDAMENTAL, KEBIJAKAN DIVIDEN DAN HARGA SAHAM SEKTOR MANUFAKTUR DI BURSA EFEK INDONESIA - Ni Made Riani (Forum Manajemen STIMI Handayani Denpasar, 2015)
Investors have the primary purpose of the funds invested into the companyto seek revenue (return) capital gain or dividend. To assess the performance ofa company in generating profits expected, investors can see from the side of itsfundamental aspect, the better the fundamental performance of a company has, thehigher the stock price of the company. This study aims to determine the effect of thefundamental factor of liquidity, leverage, profitability and dividend policy, againstfirm stock price at a manufacturing company that go public on the Indonesia StockExchange.The population in the study is a manufacturing company that distributedividends in the Indonesia Stock Exchange 2010 until 2013 with 67 companies. Thesamples were selected based on purposive sampling that pays dividends resprectivelyfrom 2010 until 2013 with 28 sample firms. The method of analysis used is the techniqueof path analysis. The results of this study are 1) Liquidity significant positive effecton Dividend Policy; 2) Leverage a significant negative effect on Dividend Policy;3) The profitability of a significant positive effect on Dividend Policy; 4) Liquiditysignificant positive effect on the firm stock price; 5) Profitability significant positiveeffect on the firm stock price, and 6) Dividend Policies significant positive effect onthe firm stock price.